Isolated obesity resistance condition or associated with aerobic exercise training does not promote cardiac impairment - Cordeiro, J. P.; da Silva, V. L. [UNESP]; Campos, D. H. [UNESP]; Cicogna, A. C. [UNESP]; Leopoldo, A. S.; Lima-Leopoldo, A. P. (FapUNIFESP (SciELO), 2021)
Mechanisms involved in cardiac function and calcium (Ca2+) handling in obese-resistant (OR) rats are still poorly determined. We tested the hypothesis that unsaturated high-fat diet (HFD) promotes myocardial dysfunction in OR rats, which it is related to Ca2+ handling. In addition, we questioned whether exercise training (ET) becomes a therapeutic strategy. Male Wistar rats (n=80) were randomized to standard or HFD diets for 20 weeks. The rats were redistributed for the absence or presence of ET and OR: control (C; n=12), control + ET (CET; n=14), obese-resistant (OR; n=9), and obese-resistant + ET (ORET; n=10). Trained rats were subjected to aerobic training protocol with progressive intensity (55–70% of the maximum running speed) and duration (15 to 60 min/day) for 12 weeks. Nutritional, metabolic, and cardiovascular parameters were determined. Cardiac function and Ca2+ handling tests were performed in isolated left ventricle (LV) papillary muscle. OR rats showed cardiac atrophy with reduced collagen levels, but there was myocardial dysfunction. ET was efficient in improving most parameters of body composition. However, the mechanical properties and Ca2+ handling from isolated papillary muscle were similar among groups. Aerobic ET does not promote morphological and cardiac functional adaptation under the condition of OR.
Keywords: Calcium handling; Exercise training; High-fat diet; Myocardial function; Obesity; Resistance to obesity